THE POLEMIC OF REVOKING REQUESTS FOR SUSPENSION OF DEBT PAYMENT OBLIGATIONS IN INDONESIA: PROCEDURAL EVALUATION AND GLOBAL PRACTICE COMPARISON - Clarita Stefanie Panjaitan; Hanif Nur Widhiyanti; Zulfahmi (CV. RADJA PUBLIKA, 2025)
The Suspension of Debt Payment Obligations as a debt restructuring instrument under Law No. 37/2004 on Bankruptcy and Suspension of Debt Payment Obligations faces procedural challenges in petition revocation practices, potentially disrupting the balance of rights between Debtors and Creditors. This study analyzes inconsistencies in the application of Article 259 of the Bankruptcy Law in revocation cases, particularly concerning creditor participation mechanisms and adherence to due process principles. An examination of Indonesian case law reveals judicial tendencies to disregard collective creditor notification and hearing requirements, alongside truncated debt verification processes prior to revocation. Key findings demonstrate that the absence of objective revocation criteria in the Bankruptcy Law contributes to judicial decision disparities. The study concludes with three systemic reform recommendations: (1) integration of measurable legal parameters for Suspension of Debt Payment Obligations revocation, (2) enhanced judicial oversight in verifying economic impacts on creditors, and (3) temporal restrictions on revocation proceedings. These findings underscore the urgent need to align the Bankruptcy Law with global best practices in debtor rehabilitation and creditor protection through independent oversight mechanisms and audited financial evidence standards.